Analysis of the Effect of ICT on Poverty Reduction at the National Level - Nur'aini, Salsabila; Wasil, Mohammad (MediaTrend, 2024)
The condition of poverty, which is not only in terms of meeting food needs but also digital poverty, makes this study aim to analyze and determine the effect of internet accessing households and mobile phone user households on poverty reduction at the national level in 2009-2021. In accordance with the Endogenous Growth Theory (The New Growth Theory), which explains the role of technological progress as an endogenous variable factor in the model and assumption framework of imperfect competition for innovation (Paul Romer, 1986). Using a quantitative approach method with secondary data in the form of time series and sourced from the Indonesian Central Bureau of Statistics. Technically, the data were analyzed using multiple linear regression analysis, classical assumption tests and statistical tests. The results showed that Information and Communication Technology (ICT), especially internet accessing households and cellular telephone user households, had a partial and simultaneous effect on reducing the poverty rate in Indonesia from 2009 to 2021. If poverty decreases, then a country's economic growth will increase.